2011
DOI: 10.1128/jvi.02538-10
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Empty Adenovirus Particles Assembled in the Absence of a Functional Adenovirus IVa2 Protein

Abstract: The molecular mechanism for packaging of the adenovirus (Ad) genome into the capsid is likely similar to that of DNA bacteriophages and herpesviruses-the insertion of viral DNA through a portal structure into a preformed prohead driven by an ATP-hydrolyzing molecular machine. It is speculated that the IVa2 protein of adenovirus is the ATPase providing the power stroke of the packaging machinery. Purified IVa2 binds ATP in vitro and, along with a second Ad protein, the L4 22-kilodalton protein (L4-22K), binds s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
62
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 51 publications
2
62
0
Order By: Relevance
“…Packaging sequence probes used in the assays contained A repeats 1 and 2, corresponding to Ad5 nt 236 to 282. The gel mobility shift assays were performed as described previously (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Packaging sequence probes used in the assays contained A repeats 1 and 2, corresponding to Ad5 nt 236 to 282. The gel mobility shift assays were performed as described previously (22).…”
Section: Methodsmentioning
confidence: 99%
“…The IVa2 and L4-22K proteins bind to the CG and TTTG motifs of the packaging repeats, respectively (11,20,21) and play an important role in viral DNA encapsidation. IVa2 and L4-22K mutant viruses produce empty particles containing no viral DNA (12,22). In vivo studies have shown that the L4-22K and IVa2 proteins are dependent on each other for binding to the packaging domain (12).…”
mentioning
confidence: 99%
“…The genome-packaging mechanism and the role of the terminase complex appear to have been conserved among double-strand DNA (dsDNA) viruses, including herpesviruses (5), adenoviruses (6), and certain bacteriophages (7). In general, the terminase complex binds the viral genomic DNA, cleaves the DNA at a specific sequence, and facilitates genome packaging into the assembling virus particle.…”
mentioning
confidence: 99%
“…Although the molecular mass of L1 52/55k calculated from its sequence is 47 kDa, the protein was named by its electrophoretic mobility; it moved as a doublet due to two different phosphorylation states (9). L1 52/55k is part of the genome packaging machinery, together with polypeptides IIIa, IVa2, L4 33k, and L4 22k (10)(11)(12)(13)(14)(15). An L1 52/55k deletion construct produces only empty capsids (10), and a thermosensitive mutation in the L1 52/55k C-terminal region (ts369; 333-EL-336 to 333-GP-336) causes partial packaging (16).…”
mentioning
confidence: 99%
“…Both the full-length and 40-kDa bands disappear and are replaced by higher-molecular-mass species in electrophoresis performed in the absence of ␤-mercaptoethanol, suggesting the formation of disulfide-linked homodimers mediated by the only Cys residue (Cys24) in L1 52/55k (9,22). The 34-kDa band has been proposed to originate by an additional cleavage at the N terminus, because it does not react with antibodies against either residues 9 to 22 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) or 402-415 in L1 52/55k, and its electrophoretic mobility is not sensitive to nonreducing conditions, a finding consistent with the absence of Cys24 (9,22).…”
mentioning
confidence: 99%